Modified Scarf Osteotomy with Medial Capsular Interposition Combined with Metatarsal Shortening Offset Osteotomy: A Comparison of Patients with Noninflammatory Arthritis and Rheumatoid Arthritis of the Foot. (20th July 2022) - Etani, Yuki; Hirao, Makoto; Ebina, Kosuke; Tsuboi, Hideki; Noguchi, Takaaki; Okamura, Gensuke; Miyama, Akira; Takami, Kenji; Nampei, Akihide; Tsuji, Shigeyoshi; Owaki, Hajime; Okada, Seiji; et al.
Abstract : Background: Patients who have noninflammatory arthritis of the feet may develop destructive changes on the first metatarsal head and painful dislocation of the metatarsophalangeal (MTP) joint of 1 or more lesser toes. This aim of this study was to compare feet with noninflammatory arthritis and those with rheumatoid arthritis (RA) with respect to the clinical and radiographic outcomes after treatment of these destructive deformities with a modified Scarf osteotomy with medial capsular interposition into the newly formed first MTP joint, combined with metatarsal shortening offset osteotomy. Methods: A retrospective observational study of 93 feet (31 with noninflammatory arthritis and 62 with RA) was performed. Hallux and lesser-toe scores on the Japanese Society for Surgery of the Foot (JSSF) scoring system, a self-administered foot evaluation questionnaire (SAFE-Q), and preoperative and postoperative radiographic parameters were evaluated. Results: There were significant improvements at the time of the final follow-up in the mean scores on the hallux and lesser-toe scales of the JSSF system and in the SAFE-Q score. The postoperative JSSF lesser-toes function score was better for the feet with noninflammatory arthritis feet than the feet with RA. There was no significant difference in the hallux valgus angle (HVA) between 1 month postoperatively and the final follow-up for both groups. Furthermore, the HVA showed a strong correlation between the 1-month and final follow-up values. Conclusions: The combination of the modified Scarf osteotomy with medial capsular interposition and shortening metatarsal offset osteotomy was useful and safe in feet with noninflammatory arthritis. The HVA at 1 month after surgery is useful to predict the HVA within 5 years after surgery. The postoperative clinical score for the lesser toes was better in the feet with noninflammatory arthritis. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.